Calvatia Species: Wild Edible Puff Balls from Amravati Region (M.S.) - Hedavoo, Ganesh B (Plantae Scientia, 2020)
India has a rich treasure of natural resources and macromycetes is one of them. Studies on wild mushrooms with special reference to their edibility, utility and medicinal value with the early references on larger fungi may be beneficial for humanity. Traditional aborigines knew the medicinal importance of edible and wild mushrooms and these are now being screened for their bioactivity in various ailments. From several bio-geographical regions of India, at least 2000 edible species of larger fungi were reported. But, the Central India region has not been investigated extensively for mushroom flora. Therefore, mycofloristic surveys were undertaken. During mycofloristic study two Calvatia species (puff-balls) viz. Calvatia cyathiformis and Calvatia fragilis were investigated from Amravati region. Reviewed literature on Calvatia species predicts that these species are new for Vidarbha (M.S.) and are edible in nature with good therapeutic potential. Edibility was confirmed by the interaction with tribal people of Korku and Pardhi community. Taxonomic identification, edibility, nutritional status and therapeutic potential of Calvatia-complex were noted by referring the standard literature. In developing countries like India, mushrooms like Calvatia are boon for progress in the fields of food, medicine and unemployment.